Molybdenum Disulphide Tape Saturable Absorber for Mode-Locked Double-Clad Ytterbium-Doped All-Fiber Laser Generation*Supported by the PPP Grant Scheme of University of Malaya under Grant No PG098-2014B. (November 2016) - Rusdi, M. F. M.; Latiff, A. A.; Hanafi, E.; Mahyuddin, M. B. H.; Shamsudin, H.; Dimyati, K.; Harun, S. W.
Abstract : We demonstrate the generation of passive mode-locked double-clad ytterbium-doped fiber laser operating in a 1-micron region. We prepare the saturable absorber from commercial crystal of molybdenum disulphide (MoS2 ). Without chemical procedure, the MoS2 is mechanically exfoliated by using a clear scotch tape. A few layers of MoS2 flakes are obtained on the tape. Then, a piece of 1 × 1 mm tape containing MoS2 thin flakes is inserted between two fiber ferrules and is integrated in the ring cavity. Stable mode-locking operation is attained at 1090 nm with a repetition rate of 13.2 MHz. Our mode-locked laser has a maximum output power of 20 mW with 1.48 nJ pulse energy. These results validate that the MoS2 has a broad operating wavelength which covers the 1-micron region, and it is also able to work in a high-power cavity.